Inhibition of opioid systems in the hypothalamus as well as the mesolimbic area suppresses feeding behavior of mice. (17th December 2015) - Ikeda, H.; Ardianto, C.; Yonemochi, N.; Yang, L.; Ohashi, T.; Ikegami, M.; Nagase, H.; Kamei, J.
Highlights: The role of mesolimbic and hypothalamic opioid receptors in feeding behavior was examined. Non-selective inhibition of opioid receptors in the NAcc, VTA and LH, but not into the VMH, decreased the food intake. Selective inhibition of μ- and δ-opioid receptors in the LH, but not in the VTA or NAcc, decreased the food intake. Selective inhibition of κ-opioid receptors in the LH and VTA, but not in the NAcc, decreased the food intake. Opioid receptors in the LH are more important in the regulation of feeding behavior than those in the mesolimbic areas. Abstract: Opioid receptors, especially μ-opioid receptors, in the ventral tegmental area (VTA) and nucleus accumbens (NAcc) are reported to regulate food motivation. However, the roles of μ-, δ- and κ-opioid receptors are not fully understood. Moreover, since μ-, δ- and κ-opioid receptors are reported to distribute in the hypothalamus, these receptors in the hypothalamus might regulate feeding behavior. Thus, the present study investigated the role of μ-, δ- and κ-opioid receptors in the VTA, the NAcc and the hypothalamus in the regulation of feeding behavior. Male ICR mice were subjected to a feeding test after food deprivation for 16 h. The mRNA levels of proopiomelanocortin (POMC), preproenkephalin (PENK) and prodynorphin (PDYN), the precursors of endogenous opioid peptides, were measured by reverse transcription-polymerase chain reaction (RT-PCR). The systemic injection of non-selective (naloxone) and selective μ (β-funaltrexamine; β-FNA), δ (naltrindole) and κ (norbinaltorphimine; norBNI) opioid receptor antagonists markedly reduced food intake. In contrast, the systemic injection of preferential μ (morphine), selective δ (KNT-127) and κ (U-50, 488) opioid receptor agonists did not change food intake. The mRNA levels of POMC, PENK and PDYN were decreased in the hypothalamus and the midbrain after food deprivation, whereas the mRNA levels of PENK and PDYN, but not POMC, were decreased in the ventral striatum. The injection of naloxone into the NAcc, VTA and lateral hypothalamus (LH), but not the ventromedial nucleus of the hypothalamus, significantly decreased food intake. The injection of β-FNA and naltrindole into the LH, but not the VTA or NAcc, decreased food intake. The injection of norBNI into the LH and VTA, but not the NAcc, decreased food intake. These results indicate that μ-, δ- and κ-opioid receptors in the LH play a more important role in the regulation of feeding behavior than those receptors in the VTA and the NAcc.